IMPLEMENTASI SCIENTIFIC LEARNING MELALUI MODEL PROJECT BASED LEARNING (PjBL) DALAM MENINGKATKAN HASIL DAN PROSES PEMBELAJARAN IPS - Asmahasanah, Salati; Rahmani, Fajar Maulidi (Program Studi PGMI, 2019)
The purpose of this study was to determine the implementation of Social Sciences Subject learning and improve student learning outcomes through the Project Based Learning (PjbL) model based on scientific learning. This research was conducted at SDIT Al-Madinah Cibinong in semester 2 of the Academic Year 2018/2019. The subject of this study was conducted in the VD class consisting of 28 students. This study used Classroom Action Research (CAR) using the Kemmis and Mc method. Taggart consists of four stages, namely planning, implementation, observation, and reflection. The results showed that with the PjBL model student learning outcomes in social studies subjects increased. This can be seen from the results of student learning tests that each cycle reaches a predetermined target. Student learning outcomes before the pre cycle are only 50% of students who are able to reach the KKM class or only 14 students while in the first cycle the percentage of achievement of student learning outcomes is 60.7% and in the results of cycle 2 is 80.1%. These results are in accordance with the target set by the researcher, which is 75%. Thus, using the Project Based Learning (PjbL) method based on scientific learning can improve student learning outcomes in social studies subjects in the fifth grade of SDIT Al-Madinah Cibinong.